The Effect of Temporary Syirkah Funds and Hajj Bailout Funds on the Profitability of Islamic Commercial Banks with Third Party Funds as a Moderating Variable - Mimma Alif Aulya; Guntur Kusuma Wardana (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2026)
The profitability of Islamic Commercial Banks (ICBs) is influenced by various funding sources, including Temporary Syirkah Funds, Hajj Bailout Funds, and Third Party Funds (TPF). This study examines the effect of Temporary Syirkah Funds and Hajj Bailout Funds on the profitability of Islamic Commercial Banks in Indonesia, with Third Party Funds (TPF) acting as a moderating variable. A quantitative approach is employed using secondary data derived from the quarterly financial statements of Islamic Commercial Banks for the period 2020-2024. The data are analyzed using panel data regression and Moderated Regression Analysis (MRA) with the assistance of EViews 12. The results indicate that Hajj Bailout Funds have a significant effect on the profitability of Islamic Commercial Banks, while Temporary Syirkah Funds do not have a significant effect. Furthermore, Third Party Funds are proven to moderate the relationship between Temporary Syirkah Funds and Hajj Bailout Funds on profitability, suggesting that the optimization of fund management particularly Third Party Funds and Hajj Bailout Funds plays a strategic role in enhancing the performance and sustainability of Islamic Commercial Banks’ profitability in Indonesia.